Community leaders and the preservation of cultural traits - Anja Prummer; Jan-Peter Siedlarek (Queen Mary University of London, School of Economics and Finance, 2016)
We explain persistent differences in cultural traits of immigrant groups with the presence of community leaders. Leaders influence the cultural traits of their community, which have an impact on the group's earnings. They determine whether a community will be more assimilated and wealthier or less assimilated and poorer. With a leader cultural integration remains incomplete. The leader chooses more distinctive cultural traits in high productivity environments and if the community is more connected. Lump sum transfers to immigrants can hinder cultural integration. These findings are in line with integration patterns of various ethnic and religious groups.
Keywords: J15; Z10; D02; 330; Cultural transmission; Leadership; Immigrants; Labor market outcomes; Social influence; Networks